FIELD TESTS OF SPILLED SOILS (Spectrum Journal of Innovation, Reforms and Development, 2023)
This article provides information on the properties of spilled soils, the amount of subsidence, self-compaction, the fact that the density of dry soil for shallower depths is higher than that of the experiment, the self-compaction characteristics of re-poured gill-like soils, as well as the field tests necessary to study the properties of spilled soils.